2005
DOI: 10.1161/circulationaha.104.510982
|View full text |Cite
|
Sign up to set email alerts
|

Trial to Evaluate the Management of Paroxysmal Supraventricular Tachycardia During an Electrophysiology Study With Tecadenoson

Abstract: Background-Tecadenoson is a potent selective A 1 -adenosine receptor agonist with a dose-dependent negative dromotropic effect on the AV node. Tecadenoson terminates induced paroxysmal supraventricular tachycardia (PSVT) without the clinically significant side effects caused by stimulation of other adenosine receptors. This trial was designed to determine a safe and effective tecadenoson bolus for termination of electrophysiologically induced PSVT. Methods and Results-Patients with a history of symptomatic PSV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 19 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…It has been tested in Phase II clinical trials for its capacity to slow heart rate in atrial fibrillation, although it has been reported to have renal toxicity. Tecadenoson (CVT-510) is a potent A 1 AR agonist with a dose-dependent negative dromotropic effect on the AV node 66 . In patient trials (now Phase III), it terminated PSVT without the side effects associated with other AR subtypes, such as hypotensive effects.…”
Section: Ars As Targets In Cardiovascular Diseasementioning
confidence: 99%
“…It has been tested in Phase II clinical trials for its capacity to slow heart rate in atrial fibrillation, although it has been reported to have renal toxicity. Tecadenoson (CVT-510) is a potent A 1 AR agonist with a dose-dependent negative dromotropic effect on the AV node 66 . In patient trials (now Phase III), it terminated PSVT without the side effects associated with other AR subtypes, such as hypotensive effects.…”
Section: Ars As Targets In Cardiovascular Diseasementioning
confidence: 99%
“…Some, such as tecadenoson, selodenoson, and PJ-875, are being developed for the treatment of supraventricular tachyarrhythmias. 29,30 Theoretically, these drugs may have several advantages over adenosine, including more sustained and selective cardiac A1 receptor effect and fewer adverse effects (eg, hypotension, flushing, bronchoconstriction, chest discomfort) in the assessment of PVs at risk of reconnection after PVI.…”
Section: Novelty and Potential Clinical Relevancementioning
confidence: 99%
“…antiarrhythmic agents, Tecadenoson [34][35][36] and Selodenoson ( Figure 1 ) [37,38] . The key structure feature that imparts high affinity and selectivity for the A 1 -AdoR comes from the N-6 lipophilic substituents: N -6-(R)-3-tetrahydrofuranyl for Tecadenoson (A 1 -AdoR K i = 3 nm) and N-6-cyclopentyl for Selodenoson (A 1 -AdoR K i = 6 nm).…”
Section: Initial Lead Compoundsmentioning
confidence: 99%